2006
DOI: 10.1080/00288233.2006.9513719
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of sheep excrement on carbon dioxide, nitrous oxide and methane fluxes in typical grassland of Inner Mongolia

Abstract: Excrement patches of grazing animals play an important role in greenhouse gas (GHG) fluxes due to the high nitrogen (N) and available carbon (C) deposited in small areas, but little information is available for the effect of excrement in the Inner Mongolian grassland (43°26 N, 116°40 E). To elucidate the effect of grazing sheep urine, fresh dung and compost on fluxes of methane (CH 4 ), carbon dioxide (CO 2 ), and nitrous oxide (N 2 O), a short-term field study (65 days) was carried out in the typical grasslan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 42 publications
4
38
3
Order By: Relevance
“…More than three fourths of all published measurements from grasslands of China were taken in the semi-arid steppe ecoregion of the NASD. Based on 306 data collected in this region we estimated the mean CH 4 uptake rate by grasslands as 74.31 AE 62.51 mg CH 4 m À2 h À1 Wang et al, 1998Wang et al, , 2000Wang et al, , 2005Ma et al, 2006;Liu et al, 2007Liu et al, , 2009aGeng et al, 2010;Zhou and Hao, 2010;Luo and Jiao, 2012), which is also the highest mean CH 4 uptake rate of grasslands for all ecoregions in China (Fig. 2).…”
Section: Observed Ch 4 Uptakes In Grasslands In Chinamentioning
confidence: 99%
See 3 more Smart Citations
“…More than three fourths of all published measurements from grasslands of China were taken in the semi-arid steppe ecoregion of the NASD. Based on 306 data collected in this region we estimated the mean CH 4 uptake rate by grasslands as 74.31 AE 62.51 mg CH 4 m À2 h À1 Wang et al, 1998Wang et al, , 2000Wang et al, , 2005Ma et al, 2006;Liu et al, 2007Liu et al, , 2009aGeng et al, 2010;Zhou and Hao, 2010;Luo and Jiao, 2012), which is also the highest mean CH 4 uptake rate of grasslands for all ecoregions in China (Fig. 2).…”
Section: Observed Ch 4 Uptakes In Grasslands In Chinamentioning
confidence: 99%
“…Thus, livestock grazing may have been the most important management of grasslands on both domains. Grazing was found to have complicated effects on CH 4 uptakes by grasslands, probably due to different grazing density and grazing patterns, or accompanied by difference of weather conditions and vegetation Wang et al, 2000;Wang et al, 2001Wang et al, , 2003bQi et al, 2003;Ma et al, 2006;Li et al, 2007;Liu et al, 2007Liu et al, , 2012cLin et al, 2009;Wan et al, 2010;Zhou and Hao, 2010;Zhou et al, 2011;Jiang et al, 2012;Zhang et al, 2012). In both semi-arid steppe ecoregion and alpine steppe and meadow ecoregion, the CH 4 uptake rate of freely grazed grasslands was lower than that of fenced grasslands (Table 1), partly due to grazing-induced changes in soil bulk density by tramping, soil nutrient and biomass allocation Qi et al, 2003;Wang et al, 2003b;Liu et al, 2007) based on 10 data).…”
Section: Observed Ch 4 Uptakes In Grasslands In Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…However, our result was lower than the mean flux in summer sheepfolds in Chen et al [27], because our measurement did not include the flux of new feces (which were cleaned out in our study) was the direct reason. Many studies had reported pronounced and short pulses of CH 4 emission immediately following application of fresh animal excreta [28,29] and livestock can be an important source of CH 4 through direct enteric emissions and decomposition of excreta deposited on grassland [30,31]. Chen et al [27] also reported that the annual budget from sheepfolds in Inner Mongolia is mainly driven by emissions during the growing season, with most of these emissions occurring in the summer sheepfold.…”
Section: Ch 4 Flux From Sheepfoldsmentioning
confidence: 99%